1999
DOI: 10.1007/s002470050564
|View full text |Cite
|
Sign up to set email alerts
|

Complete duplication of bladder and urethra in the coronal plane in a girl: case report and review of the literature

Abstract: An unusual case of complete duplication of the bladder and urethra in the coronal plane associated with left ectopic kidney, duplication of the clitoris and a chondrolipomatous malformation in the pelvic region in a girl is reported. The accessory bladder was located posterolateral to the normal bladder and a ureteric opening into the accessory bladder was found. The malformation was initially identified by US and cystography and confirmed by cystoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 10 publications
0
32
0
2
Order By: Relevance
“…Berrocal and et al [8] identified the following anomalies: duplication of the external genitalia in 30% of cases; duplication of the lower gastrointestinal tract, including anomalies such as stenosis, atresia and ectopic rectum, in 40% of cases, and duplication of the spinal medulla, including anomalies of the nervous system such as meningocele, and fistula between the bladder and the rectum and the vagina and urethra, which should be monitored for in patients with a sagittal septum, in 10% of cases. Therefore, the gastrointestinal system, genitourinary system and columna vertebralis of these cases should be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Berrocal and et al [8] identified the following anomalies: duplication of the external genitalia in 30% of cases; duplication of the lower gastrointestinal tract, including anomalies such as stenosis, atresia and ectopic rectum, in 40% of cases, and duplication of the spinal medulla, including anomalies of the nervous system such as meningocele, and fistula between the bladder and the rectum and the vagina and urethra, which should be monitored for in patients with a sagittal septum, in 10% of cases. Therefore, the gastrointestinal system, genitourinary system and columna vertebralis of these cases should be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Some children present in the newborn period with urinary tract infection, abnormalities of the external genitalia and anorectal anomalies, while others can remain asymptomatic for many years [3,4]. The most accepted theory related to its etiology is partial twinning of the caudal end of the embryo in association with the formation of an abnormal sagittal septum [5].…”
Section: Discussionmentioning
confidence: 98%
“…Various anatomies of this malformation range from partial duplication of the bladder to complete duplication of the lower urinary tract [2,3,6]. Two bladders are usually side-by-side and separated by Postoperative IVP shows a normal upper urinary system and bladder a peritoneal fold of varying depth.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…En nuestro país, en los últimos 20 años se han publicado 18 casos 1,2,3,4,5 , de los cuales la inmensa mayoría son varones, siendo descrita esta patología tan solo en 2 niñas 6,7 . Presentamos el caso de un varón que consultó por la presencia de un doble orificio uretral y hacemos un breve repaso de esta inusual patología.…”
unclassified